Spermiogenesis and sperm ultrastructure in ten species of Loricariidae (Siluriformes, Teleostei) - Spadella, Maria Angelica; Oliveira, Claudio [UNESP]; Quagio-Grassiotto, Irani [UNESP] (Springer, 2012)
The current study describes the ultrastructural characteristics of spermatogenesis, spermiogenesis, and spermatozoa in specimens of siluriform taxa Neoplecostominae, Hypoptopomatinae, Otothyrinae, Loricariinae, and Hypostominae. Our data show that the characteristics of spermatogenesis and spermiogenesis and spermatozoa ultrastructure of Neoplecostominae are more common to Hypoptopomatinae and Otothyrinae than to Loricariinae and Hypostominae. Furthermore, Loricariinae and Hypostominae have more characteristics in common than with any other group of Loricariidae. These data reinforce the phylogenetic hypotheses of relationships among the subfamilies of Loricariidae. Considering the available data in Loricarioidei, Loricariidae presents ultrastructural characteristics of spermatogenesis and spermiogenesis that are also observed in Astroblepidae, its sister group. However, the most of the characteristics of spermatozoa ultrastructure found in Astroblepidae are also observed in Scoloplacidae, the sister group of a clade composed of Astroblepidae and Loricariidae.
Keywords: Catfish; Gametogenesis; Spermatids; Male germ cell; Morphology